(untitled) (Journal of International Studies, 2020)
Consular relations are as essential in inter-state relation as diplomatic relations, although theirs are focussed on servicing the people or corporate bodies overseas. Nevertheless, the conduct of consular relations is not as simple as most people think for prior to the Vienna Convention on Consular Relations (hereinafter, VCCR), 1963, there existed numerous consular treaties. Nor does the service receive as much attention as diplomatic relations. This article examines the factors that gave rise to these situations, which were traced as far back to ancient times with the implementation of the "personality of laws". The emergence of the modem European states had not diminished the practice of providing "customised" jurisdiction for consular agents or officers although states have become more territorial. Conscious effort to bring about some uniformity in consular law and, thus, reduce the confusion that arose from the diversified consular functions and jurisdiction came about only in the twentieth century.